2021
DOI: 10.1038/s41598-021-01471-4
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of seagrass habitat and community diversity in the Great Barrier Reef World Heritage Area

Abstract: The Great Barrier Reef World Heritage Area (GBRWHA) in north eastern Australia spans 2500 km of coastline and covers an area of ~ 350,000 km2. It includes one of the world’s largest seagrass resources. To provide a foundation to monitor, establish trends and manage the protection of seagrass meadows in the GBRWHA we quantified potential seagrass community extent using six random forest models that include environmental data and seagrass sampling history. We identified 88,331 km2 of potential seagrass habitat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Specifically, the organic content found within the mud substrate at the Orongan and Matahari sites appeared to be beneficial for seagrass diversity. This finding aligns with previous research that has identified substrate type as a key determinant of seagrass diversity across various spatial scales and bioregions (Carter et al 2021;Short et al, 2007).…”
Section: Correlation Dominant Substrate Type With Alpha Diversitysupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, the organic content found within the mud substrate at the Orongan and Matahari sites appeared to be beneficial for seagrass diversity. This finding aligns with previous research that has identified substrate type as a key determinant of seagrass diversity across various spatial scales and bioregions (Carter et al 2021;Short et al, 2007).…”
Section: Correlation Dominant Substrate Type With Alpha Diversitysupporting
confidence: 92%
“…These findings align with the influence of geographical factors on seagrass diversity discussed in the Great Barrier Reef study (Carter et al, 2021). This study highlighted the strong effect of latitude on the probability of seagrass presence (Short et al, 2007), with seagrass being more likely to occur at latitudes >18° S (Carter et al, 2021).…”
Section: Alpha Diversity Relationship With Constrain Variablessupporting
confidence: 86%
See 1 more Smart Citation
“…The immediate scientific value of projects like this have been demonstrated on Queensland's east coast, where the Great Barrier Reef World Heritage Area (GBRWHA) data synthesis (Carter et al 2021 a ) has been used to answer a number of key ecological questions, including the probability of seagrass distribution and communities (Carter et al 2021 d ), defining the desired state of seagrass communities in the Townsville region (Collier et al 2020) and GBRWHA (Carter et al 2022 b ), examining management targets for rivers influencing seagrass habitat (Collier et al 2021; Lambert et al 2021), and in designing a Great Barrier Reef‐scale monitoring program (Udy et al 2019). Seagrass data has also been used on the Great Barrier Reef to model risk exposure (Grech et al 2011; Grech et al 2012; Bainbridge et al 2018); propagule distribution (Grech et al 2016; Schlaefer et al 2022); developing a National Ocean Account in Australia (https://www.abs.gov.au/articles/towards-national-ocean-account); and connectivity among meadows (Tol et al 2017; Grech et al 2018).…”
Section: Data Use and Recommendations For Reusementioning
confidence: 99%
“…The generated and freely available maps for each state are available at https://portal.tern.org.au/robert-franklin-ccanto/19365 and all have the acronym ACEAS at the end of the file name (Canto et al, 2014a,b,c,d,e,f,g). Then additional sources were added to this map (QDPI-F, 2009;McKenzie et al, 2014;TropWATER, 2016). The deep water seagrass map (QDPI-F, 2009) was categorized as the probability of seagrass occurrence.…”
Section: Seagrass Map Generationmentioning
confidence: 99%